Father-daughter relationship and eating disorders: a review of the scientific production - Santos, Manoel Antônio dos (2019)
We investigated the scientific production dedicated to the analysis of the relationship between daughters with eating disorders and their fathers. An integrative review was performed on PsycINFO, CINAHL, PubMed and LILACS databases. We reviewed studies published between January 2000 and June 2014. Twenty-seven studies were included in the review. Most were from European countries and were comprised of quantitative studies. An unstable relationship with the father figure and an emotionally distant relationship between father and daughter were recurring themes in the selected publications. Studies showed the importance of investigating and ensuring the participation of fathers in the treatment of eating disorders, but none of them investigated father involvement in terms of assistance. Further research is needed in order to explore qualitative studies in the Brazilian context.